A Middleware for the Development of Distributed Collaborative Video Applications - Oliveira Neto, João Martins de; Silva, Lincoln David Nery e (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Remote video applications over the internet have been a trend for the last few years. As they grew in popularity, several areas of knowledge have started to take advantage of their functionalities and the possibility to make collaborative environments using video arose. From videoconferences to educational telemedicine video streamings, these collaborative applications are usually hard and tedious to configure and deploy and usually limit the number of participants. This work proposes a scalable architecture for collaborative video applications that makes the development and deployment of collaborative video applications easier and supports a high number of users simultaneously producing and consuming video in these applications.